2020
DOI: 10.2147/ott.s240619
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-483 Targeted SOX3 to Suppress Glioma Cell Migration, Invasion and Promote Cell Apoptosis</p>

Abstract: Objective: Glioma is the most common malignant brain tumor that has high aggressiveness. The aim of this study was to investigate the potential therapeutic targets for gliomas. Materials and Methods: Real-time quantitative polymerase chain reaction (RT-qPCR) was employed to calculate the expression of miRNA and genes. The connection between the expression of miR-483 and patients' overall survival rate was evaluated using Kaplan-Meier analysis. In addition, the underlying mechanism was detected using luciferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…To the best of our knowledge, in this study, miR1258 was found to be highly expressed in preterm infants with BPD for the first time and was identified as a risk factor for BPD. Furthermore, miR-483 may inhibit the proliferation and metastasis of glioma and colorectal cancer [ 44 , 45 ]. It has been demonstrated that miR-483 targets insulin-like growth factor 1 (IGF1) and downregulates the expression of key proteins in the PI3K/AKT signalling pathway, thereby inhibiting myogenic cell proliferation and differentiation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, in this study, miR1258 was found to be highly expressed in preterm infants with BPD for the first time and was identified as a risk factor for BPD. Furthermore, miR-483 may inhibit the proliferation and metastasis of glioma and colorectal cancer [ 44 , 45 ]. It has been demonstrated that miR-483 targets insulin-like growth factor 1 (IGF1) and downregulates the expression of key proteins in the PI3K/AKT signalling pathway, thereby inhibiting myogenic cell proliferation and differentiation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies have shown that overexpression of SOX3 is associated with poor overall survival in gastric cancer, 42 breast cancer 43 and adult de novo acute myeloid leukaemia. 44 Lu S et al 45 indicated that overexpression of SOX3 predicts a poor outcome in GBM patients; and, Sa JK et al 46 found SOX3 is associated with tumour invasiveness, malignancy and poor prognosis in GBM patients. Vicentic et al 47 found SOX3 can accelerate the malignant behaviour of GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis revealed that all three SOXB1 members were upregulated in GBM to varying degrees, compared to the normal tissues, identifying only SOX3 as a potential prognostic biomarker whose increased expression correlated with better overall survival [ 38 ]. In contrast, Lu et al revealed a significantly higher expression level of SOX3 in glioma compared with the normal tissues and correlated its overexpression with poor outcomes [ 40 ]. Our previous study revealed a higher level of SOX3 expression in a subset of primary GBM samples compared to non-tumoral brain tissues and in a patient-derived GSC culture, suggesting that SOX3 is required to maintain GSCs in an undifferentiated state [ 41 ].…”
Section: The Role Of Sox Genes In Glioblastomamentioning
confidence: 99%